Manuscript Investigation in the Sinai II Project - Hollaus, Fabian; Camba, Ana; Fiel, Stefan; Saleem, Sajid; Sablatnig, Robert (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
This work is concerned with the analysis of historical manuscripts.The manuscripts investigated are partially in a bad condition, due to their age, bad storage conditions etc. These circumstances impede a transcription of the ancient writings, as well as the application of document image analysis methods. Therefore, the writings are imaged with a portable MultiSpectral Imaging acquisition system. By using this non-invasive investigation technique the contrast of the degraded and faded-out writings can be enhanced. In order to gain a further contrast enhancement, a post-processing method has been developed.Additionally, two document analysis methods have been developed in order to facilitate the work of scholars: First, an Optical Character Recognition is described. Second, a method designed for the automated identification of writers of ancient Slavic manuscripts is explained. This paper provides an overview on the manuscript investigation techniques mentioned.